The effect of instructor stance on ESL speakers' language production in a conversation group setting. (December 2015) - Hernández González, Teresa; McDonough, Kim
Abstract: Numerous approaches to second language teaching emphasize the important role of instructors in eliciting extended language production from their students (Walsh, 2011; Wong & Waring, 2010 ). To shed light on the relationship between instructors' elicitation techniques and student talk, the current study analyzed the content exchanges initiated by preservice instructors ( N = 19) during conversation group discussions. More specifically, this study examines how the instructor's stance (evaluative or non-evaluative) affected the language production of the ESL speakers. The findings indicated that non-evaluative exchanges elicited more student talk than evaluative exchanges. Additional insight into the relationship between stance and student responses to instructor-initiated exchanges is provided through excerpts from the conversation groups. Implications are discussed in terms of raising preservice instructors' awareness of social positioning and its impact on student interaction.